A new and three known species of the genus Tylencholaimellus Cobb in M.V. Cobb, 1915 (Nematoda: Dorylaimida) from Changbai Mountain, China - Zhang, Min; Ahad, Sumaya; Baniyamuddin, M.; Liang, Wenju; Ahmad, Wasim (Zootaxa, 2012)
A new and three known species of the genus Tylencholaimellus Cobb in M.V. Cobb, 1915 are described from ChangbaiMountain, Northeast China. Tylencholaimellus sinensis n. sp. species is characterized by having a medium sized body (L=1.1–1.3 mm); outer cuticle with fine transverse striations; inner layer distinctly striated; radial refractive elementsabundant; labial disc absent; lip region offset by constriction; lips rounded and amalgamated; odontostyle 18–19 µm,odontophore 7–8 µm, combined length 25–27μm; anterior uterine sac 0.8–1.6 mid body diameters long; mono-opisthodelphic female genital system with small anterior uterine sac; transverse vulva and short conoid tail.Tylencholaimellus striatus Thorne, 1939, T. montanus Thorne, 1939 and T. cinctus Orr & Dickerson, 1965 are described for the first time from this region of the world.